2008
DOI: 10.1074/jbc.m804645200
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Ncb5or Results in Impaired Fatty Acid Desaturation, Lipoatrophy, and Diabetes

Abstract: Targeted ablation of the novel flavoheme reductase Ncb5or knock-out (KO) results in progressive loss of pancreatic ␤-cells and white adipose tissue over time. Lipoatrophy persisted in KO animals in which the confounding metabolic effects of diabetes were eliminated by islet transplantation (transplanted knockout (TKO)). Lipid profiles in livers prepared from TKO animals were markedly deficient in triglycerides and diacylglycerides. Despite enhanced expression of stearoyl-Co-A desaturase-1, levels of palmitolei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 52 publications
3
33
0
Order By: Relevance
“…Wildtype cells treated for 12 h with tunicamycin (1 g/ml) were used acids. Although it was not technically feasible to carry out in vitro experiments on isolated pancreatic ␤ -cells, we did show that the viability of isolated Ncb5or Ϫ / Ϫ hepatocytes was markedly impaired and apoptosis enhanced by incubation with palmitate but not with oleate or a mixture of palmitate and oleate ( 7 ). There is growing evidence that in a number of cell types ( 8,9 ), including pancreatic ␤ -cells ( 10 ), the ER is a target of lipotoxicity induced by palmitate.…”
Section: Mouse Hepatocyte Isolation and Cell Culturementioning
confidence: 96%
See 2 more Smart Citations
“…Wildtype cells treated for 12 h with tunicamycin (1 g/ml) were used acids. Although it was not technically feasible to carry out in vitro experiments on isolated pancreatic ␤ -cells, we did show that the viability of isolated Ncb5or Ϫ / Ϫ hepatocytes was markedly impaired and apoptosis enhanced by incubation with palmitate but not with oleate or a mixture of palmitate and oleate ( 7 ). There is growing evidence that in a number of cell types ( 8,9 ), including pancreatic ␤ -cells ( 10 ), the ER is a target of lipotoxicity induced by palmitate.…”
Section: Mouse Hepatocyte Isolation and Cell Culturementioning
confidence: 96%
“…We previously reported that primary hepatocytes from Ncb5or Ϫ / Ϫ (KO) mice had impaired viability and enhanced apoptosis, analyzed by TUNEL, following 1 h and 4 h exposure to 1.0 mM palmitate but not to 1.0 mM oleate or an equimolar mixture of the two fatty acids ( 7 ). With a greatly improved method for cell isolation, we are now able to obtain cells at much higher yields and improved viability, allowing longer incubation times.…”
Section: Palmitate Impairs Cell Viability and Induces Apoptosis Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Ncb5or deficiency in hepatocytes results in an impaired ⌬9 desaturation pathway, and saturated FA induced lipotoxicity is observed (12). Ncb5or knock-out mice have usual embryonic and fetal growth, and normal viability at birth with no gross anatomic abnormalities (31).…”
Section: Fatty Acid Desaturases (Fads)mentioning
confidence: 99%
“…Ncb5or is an endoplasmic reticulum-bound protein that has been implicated in lipid metabolism and diabetes (11,12). Ncb5or contains two redox domains; the amino-terminal portion is highly homologous to classical microsomal cytochrome b 5 , and the carboxyl-terminal portion of the protein is highly similar to cytochrome b 5 reductase domain (10).…”
Section: Fatty Acid Desaturases (Fads)mentioning
confidence: 99%